The methodological quality of systematic reviews of animal studies in dentistry - Faggion Junior, Clóvis Mariano; Listl, Stefan; Giannakopoulos, Nikolaos Nikitas (The veterinary journal, 2012)
Systematic reviews and meta-analyses of animal studies are important for improving estimates of the effects of treatment and for guiding future clinical studies on humans. The purpose of this systematic review was to assess the methodological quality of systematic reviews and meta-analyses of animal studies in dentistry through using a validated checklist. A literature search was conducted independently and in duplicate in the PubMed and LILACS databases. References in selected systematic reviews were assessed to identify other studies not captured by the electronic searches. The methodological quality of studies was assessed independently and in duplicate by using the AMSTAR checklist; the quality was scored as low, moderate, or high. The reviewers were calibrated before the assessment and agreement between them was assessed using Cohen’s Kappa statistic. Of 444 studies retrieved, 54 systematic reviews were selected after full-text assessment. Agreement between the reviewers was regarded as excellent. Only two studies were scored as high quality; 17 and 35 studies were scored as medium and low quality, respectively. There is room for improvement of the methodological quality of systematic reviews of animal studies in dentistry. Checklists, such as AMSTAR, can guide researchers in planning and executing systematic reviews and meta-analyses. For determining the need for additional investigations in animals and in order to provide good data for potential application in human, such reviews should be based on animal experiments performed according to sound methodological principles.